THERMAL AGING STUDY OF BIODEGRADABLE POLYMER MATERIALS BY DIELECTRIC THERMAL ANALYSIS - Porjazoska Kujundziski, A.; Chamovska, D. (Journal of Engineering & Processing Management, 2015)
Two different studies of the thermal aging of polyesters based on lactic and glycolic acids were compared. Thermal degradation of poly(L-lactic acid) (PLLA), poly(L-lactic acid-co-glycolic acid) (PLLGA) and poly(DL-lactic acid-co-glycolic acid) (PDLGA) was studied by the dielectric thermal analysis (DETA). The aging was performed at 37 0C in vacuum oven. The dielectric features i.e., dielectric permittivity,, dielectric losses,, and phase lag, tg , were determined by PL-DETA containing a parallel plate capacitance cell, from the room temperature to 80 0, 150 0, and 180 0 C, at the heating rates of 2 and 3 0 Cmin-1 . Dielectric scans were obtained at a frequency of 1 kHz and a.c. signal of 200 mV. Different behavior of PLLA, PLLGA, and PDLGA during degradation was observed. As the aging of PDLGA proceeds, dielectric losses shift to the lower temperatures, indicating existence of lower molecular weights.  - T, and tg  - T dependences of PLLGA, as well as those for PLLA show two simultaneous processes occurring, crystallization and degradation.